2000
DOI: 10.1590/s0004-282x2000000500015
|View full text |Cite
|
Sign up to set email alerts
|

Malformações do sistema nervoso central: análise de 157 necrópsias pediátricas

Abstract: RESUMO -As malformações do sistema nervoso central (SNC) têm sido relatadas como de alta prevalência, acometendo 5 a 10 crianças para 1000 nascidos vivos. Estudamos a frequência das malformações do SNC em 5837 necrópsias pediátricas realizadas no Serviço de Anatomia Patológica do Hospital de Clínicas-UFPR, entre 1960 e 1995. Encontraram-se 157 malformações do SNC, correspondendo a 2,69% das necrópsias. As malformações mais comuns foram os defeitos do tubo neural (61%), incluindo 47 anencefalias e 45 casos clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
7
0
10
Order By: Relevance
“…A similar result was obtained in Massachusetts in the USA, 13 where a comparison of the cause of death on death certifi cates with autopsy results demonstrated that a portion of deaths indicated as asphyxia on death certifi cates, were subsequently considered as unknown following autopsy. Perinatal autopsies performed in a referral hospital in Curitiba 19 found 15.7% of fetal deaths as unspecifi ed.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was obtained in Massachusetts in the USA, 13 where a comparison of the cause of death on death certifi cates with autopsy results demonstrated that a portion of deaths indicated as asphyxia on death certifi cates, were subsequently considered as unknown following autopsy. Perinatal autopsies performed in a referral hospital in Curitiba 19 found 15.7% of fetal deaths as unspecifi ed.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of hair follicles starts in the eighth week, and in the 12th week, the development of embryonic fibroblasts is organized in networks of collagen fibers [3, 4]. …”
Section: The Human Skinmentioning
confidence: 99%
“…As 157 malformações do sistema nervoso central (SNC) representaram 13,06% das malformações gerais e estiveram presentes em 2,69% do total de necrópsias estudadas 13 . As necrópsias foram avaliadas e parâmetros como sexo, idade, e presença de outras malformações associadas foram compilados em planilha.…”
Section: Métodounclassified
“…Este valor de "p" indica uma tendência das malformações do SNC ocorrerem no sexo feminino. A explicação para este fato se dá quando se verifica que defeito do tubo neural, malformação do SNC mais frequente, é mais prevalente no sexo feminino 13 . Em nossa amostra a predominância foi do sexo masculino (2,67:1).…”
Section: Malformações Renaisunclassified